Uptake of Tenofovir-Based Antiretroviral Therapy among HIV–HBV-Coinfected Patients in the EuroSIDA Study. Issue 5 (July 2018) - Peters, Lars; Mocroft, Amanda; Grint, Daniel; Moreno, Santiago; Calmy, Alexandra; Jevtovic, Djordje; Sambatakou, Helen; Lacombe, Karine; Wit, Stephane De; Rockstroh, Jürgen; Smidt, Jelena; Karpov, Igor; et al.
Background: According to guidelines all HIV–HBV-coinfected patients should receive tenofovir-based combination antiretroviral therapy (cART). We aimed to investigate uptake and outcomes of tenofovir-based cART among HIV–HBV patients in the EuroSIDA study. Methods: All hepatitis B surface antigen (HBsAg)+ patients followed up after 1 March 2002 were included. Changes in the proportion taking tenofovir-based cART over time were described. Poisson regression was used to investigate the relationship between tenofovir use and clinical events. Results: 953 HIV–HBV patients were included. Median age was 41 years and patients were predominantly male (85%), White (82%) and ART-experienced (88%). 697 and 256 were from Western and Eastern Europe, respectively. 55 started cART during follow-up, the proportion starting with CD4 + T-cell count <350 cells/mm 3 decreased from 85% to 52% in the periods 2002–2006 to 2007–2015. Tenofovir use, among those taking cART, increased from 4% in 2002 to 73% in 2015. Compared to West, tenofovir use was lower in East in 2005 (7% versus 42%), and remained lower in 2015 (63% versus 76%). Among 602 patients taking tenofovir-based cART during follow-up, 155 (26%) discontinued tenofovir. 27 of all discontinuations were due to adverse effects. Only 14 started entecavir and/or adefovir after tenofovir discontinuation, whereas 10 started pegylated interferon. Tenofovir use was not significantly associated with lower risk of liver-related clinical events ( n =51), adjusted incidence rate ratio (IRR) 0.64 (95% CI 0.35, 1.18) for comparing patients on tenofovir with those off tenofovir. Conclusions: Although use of tenofovir-based cART among HIV–HBV patients has increased across Europe, a substantial proportion are still starting cART late and are receiving suboptimal HBV therapy.